Campus universitario en Soacha (2020)
Nowadays, Soacha is one of the municipality presents higher déficit in high education coverage in the metropolitan area of Bogotá, which causes the affected population have to displace to other cities like Bogotá where there is a greater educational offer to access to equipments that provide this service. The University Campus in Soacha is an architectural project in order to respond to municipality’s high educational needs , through 8 methodological phases that allow to do an analysis and diagnosis in the Soacha municipality to understand the operation of the territory and the needs that present there. As a final result, an equipament of high education is proposed, it´s characterized to have a compact typology and it groups not only educational activities but complementary and recreational activities, which respond to the territory vocation and to the knowledge areas that have higher demand unmet in the municipality. In the same way, the Project responds to the indicators established in en UI GreenMetric World University Ranking with the purpouse of promote the sustainable development in the university campus.